China-US Competition Impact on Small and Middle Powers' Strategic Choices - Grano, Simona A.; Huang, David Wei Feng (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This edited volume is a collection of chapters by noted scholars of US-China relations as well as regional experts on Europe and East Asia. It makes a major contribution to our understanding of the impacts of great power competition on the middle powers in the two most important and dynamic areas of the world. All chapters are clearly written and original, providing fresh and unique insights into the complicated issues in the contemporary world. Strongly recommended for anyone who is interested in the great power relations and regional dynamics in Asia and Europe." --Suisheng Zhao, Professor, Josef Korbel School of International Studies, University of Denver, and Editor of Journal of Contemporary China. "Focusing on two uniquely important countries, the US and China, and the spillover effects of their competition on middle powers and smaller states in Europe and East Asia, the contributors have produced a volume that offers valuable comparative insights and fresh perspectives on the defining great power competition of our era." --Jacques deLisle is Professor of Law and Political Science, and Director of the Center for the Study of Contemporary China, at the University of Pennsylvania Carey Law School, USA. This open access edited book brings together a closer examination of European and Asian responses to the escalating rivalry between the US and China. As the new Cold War has surfaced as a perceivable reality in the post-COVID era, the topic itself is of great importance to policymakers, academic researchers, and the interested public. Furthermore, this manuscript makes a valuable contribution to an under-studied and increasingly important phenomenon in international relations: the impact of the growing strategic competition between the United States and China on third parties, such as small and middle powers in the two arguably most affected regions of the world: Europe and East Asia. Simona A. Grano is Senior Lecturer and Director of the Taiwan Studies Project at the University of Zurich. David Wei-Feng Huang is Associate Research Fellow at Academia Sinica, Taiwan.